Reaffirming the Role of Anthropology in Transformative Change: Responses, Resonance, and Seizing Opportunities - Larsen, Peter Bille; Tibet, Eda Elif; Poltorak, Mike (Swiss Journal of Sociocultural Anthropology, 2025)
This brief response to reviews of the Ascona Charter asks how it resonates with and connects diverse realities, concerns, and experiences of transformation. The Charter responds to a collective call from students and engaged scholars for adopting collective action that prioritizes transformation and positive change in the world, rather than remaining caught in neoliberal metrics and individualized trajectories. By operationalizing the Charter’s values, anthropology can reclaim its relevance and contribute meaningfully to addressing the triple planetary crisis. Through embracing multimodal approaches, fostering ethical partnerships, and advocating for systemic change, anthropologists can play a pivotal role in addressing the pressing challenges of our time.